Magnetism : A Very Short Introduction - Blundell, Stephen (Oxford: Oxford University Press, 2012)
"In this Very Short Introduction, Stephen J. Blundell illuminates the mysterious force of magnetism. For centuries, magnetism has been used for various purposes--through compasses it gave us the ability to navigate, and through motors, generators, and turbines, it has given us power. Blundell explores our understanding of electricity and magnetism, from the work of Galvani, Ampere, Faraday, and Tesla, and describes how Maxwell and Faraday's work led to the unification of electricity and magnetism--one of the most imaginative developments in theoretical physics. Finally, he discusses the relationship between magnetism and relativity, quantum magnetism, and its impact on computers and information storage, showing how magnetism has changed our fundamental understanding of the Universe." -- Publisher's description.
Mysterious attraction? -- The Earth as a magnet -- Electrical current and the path to power -- Unification -- Magnetism and relativity -- Quantum magnetism -- Spin -- The magnetic library -- Magnetism on Earth and in space -- Exotic magnetism -- Mathematical appendix.
Includes bibliographical references (pages 135-136) and index.
Keywords: Magnetism; Physics